1994
DOI: 10.1111/j.1559-1816.1994.tb02365.x
|View full text |Cite
|
Sign up to set email alerts
|

Practice and Persuasive Frame: Effects on Beliefs, Intention, and Performance of a Cancer Self‐Examination1

Abstract: Many behaviors are performed less frequently than intended because they require knowledge and skill to overcome behavioral barriers. This experiment tested effects of two factors, direct experience and message frame, that were hypothesized to affect men's intention to perform the testicle self-exam for cancer (TSE) and their actual exam performance, in part by affecting their knowledge and beliefs about overcoming TSE performance barriers. Men's experience performing the TSE on a life-like model and the frame … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 42 publications
(25 reference statements)
0
29
0
1
Order By: Relevance
“…Several studies have attempted to discover the best methods for men to learn about testicular cancer, the TSE, and how to perform it. For example, increased TSE performance was found for men who had the opportunity to practice performing the TSE on a life-like model (Steffen, Sternberg, & Teegarden, 1994; see also Neef, Scutchfield, Elder, & Bender, 1991;Steffen & Grubber, 1991). Furthermore, Katz et al, (1995) found the best predictors of cancer awareness and self examination were fear of developing cancer and the self-rated confidence that the self-exam was being done correctly.…”
Section: Promoting the Tsementioning
confidence: 95%
“…Several studies have attempted to discover the best methods for men to learn about testicular cancer, the TSE, and how to perform it. For example, increased TSE performance was found for men who had the opportunity to practice performing the TSE on a life-like model (Steffen, Sternberg, & Teegarden, 1994; see also Neef, Scutchfield, Elder, & Bender, 1991;Steffen & Grubber, 1991). Furthermore, Katz et al, (1995) found the best predictors of cancer awareness and self examination were fear of developing cancer and the self-rated confidence that the self-exam was being done correctly.…”
Section: Promoting the Tsementioning
confidence: 95%
“…Differences between studies in participants' numeracy skills because of the use of convenience samples and nonprobabilistic sampling methods could possibly explain why some reported no framing effects, [48][49][50][51][52][53][54] whereas others found strong effects of message frames. 10,[35][36][37][38] More importantly, our study is unique in its efforts to investigate whether visual aids can overcome framing effects when communicating important health information in participants who were disadvantaged by their lack of numerical skills: When visual aids were added to the numerical information about the risk of the surgical procedure, framing was reduced or disappeared in participants with low numeracy.…”
Section: Discussionmentioning
confidence: 99%
“…42 Similarly, people with low numeracy-who have difficulties grasping numerical concepts necessary for understanding risk communications [43][44][45] -are more susceptible to framing than those with high numeracy. 46,47 Other studies, however, reported no differences between framing conditions or even found framing effects in the opposite direction to that hypothesized ( [48][49][50][51][52][53][54] ; see 55,56 for reviews), leaving open a number of important questions related to the effects of different health message frames. First, to the best of our knowledge all the studies about framing were conducted on convenience samples of specific groups of participants (e.g., patients with particular diseases or students [2][3][4][5][6] ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, in a randomized trial, Lerman, Ross, Boyce, Gorchov et al (1992) found no difference for positively versus negatively framed booklets on adherence to subsequent annual mammography among women with prior abnormal mammograms (but both experimental groups showed greater adherence (66 -67%) than the control conditions (53 -55%). In a study similar to that of the Meyerowitz and Chaiken (1987) BSE study, Steffen, Sternberg, Teegarden, and Shepherd (1994) found no framing effects for testicle self-examination (TSE). Tykocinski, Higgins, and Chaiken (1994) found no difference for framing overall, but a significant interaction with the personality construct of self-discrepancy.…”
mentioning
confidence: 93%